Identification and Distribution of Soil Transmitted Helminths around The Shed and Grazing Fields of Madura Cattle in Sub-District of Geger, Bangkalan Regency - Dewi Mahartina; Poedji Hastutiek; Sri Mulyati; Soeharsono Soeharsono; Muhammad Hambal (Journal of Parasite Science (JoPS), 2020)
This research aims to determine the percentage and kind of Soil Transmitted Helminths contamination in around the shed and grazing field soil of Madura cattle in Sub-District of Geger, Bangkalan District. The research was conducted on July until September 2018. The method of this research used a non-experimental method and through an observation study. The sample of this study is 100 samples of around the shed and grazing field soil, then examined in the laboratory of Helminthology, Division of Parasitology, Faculty of Veterinary Medicine, Universitas Airlangga used Modifed Sucrose 58%. Based on the kind of contamination, the highest contamination was Toxocara sp. (45.9%). Followed by Strongyloides sp. (41.4%), Trichuris sp. (9.5%) and Ancylostoma sp. (3.2%). Based on location, the percentage of grazing fields was higher (70%) than around the shed (50%). The result of statistical analysis using Chi- Square test showed significant differences in the percentage between around the shed and grazing field soil (p<0.05).